Mechanically Robust SiAlON Ceramics with Engineered Porosity via Two-step Sintering for Applications in Extreme Environments. Issue 17 (2016) - Chi, Ike Suchih; Bux, Sabah K.; Bridgewater, Marjorie M.; Star, Kurt E.; Firdosy, Samad; Ravi, Vilupanur; Fleurial, Jean-Pierre
ABSTRACT: Porous ceramics have been widely used under extreme environments due to their high strength, good thermal shock resistance, and excellent corrosion resistance. Recently, silicon aluminum oxynitride (SiAlON) ceramic, a solid solution of Si3 N4 with AlN, SiO2, and Al2 O3, attracted our interest because of its superior mechanical and physical properties for applications under extreme environments (i.e., high temperature, high pressure, excellent mechanical wear, and low PH). However, in spite of its many unique properties, porous SiAlON production has not been scaled up sufficiently to meet industrially relevant quantities due to its high synthesis cost and the difficulty of manufacturing articles. Here, we report on a scalable two-step carbothermal reduction and nitridation (CRN) method to synthesize mechanically robust SiAlON ceramic materials with controlled porosity levels. The morphologies and chemical composition of the synthesized porous SiAlON ceramics were characterized using SEM, XRD, EDAX, and microprobe analysis. In addition, the flexural strength of the engineered porous SiAlON ceramics is also reported in this paper.